Kompres Hangat Aromaterapi Lavender Pada Remaja Putri Yang Mengalami Dismenorea Di Pondok Pesantren Al-Ma’ruf Kota Kediri - Shinta Kristianti; Triatmi Andri Yanuarini; Lailatul Khusna (Akademi Keperawatan Dharma Husada Kediri, 2018)
Dysmenorrhea is a disorder of menstrual flow or menstrual pain. In Indonesia the figure is estimated to be 55% of women of childbearing age who are tormented by pain during menstruation. Approximately 70-90% of cases of menstrual pain occur during adolescence and adolescents who experience menstrual pain will be affected academic, social and sports activities. This study aims to determine differences in the level of dysmenorrhea before and after given warm compresses of aromatherapy lavender in girls. The design of this study was pre-experimental with one group pretest-posttest design. A simple random sampling technique was obtained by a sample of 49 people who were administered on 13 June to 18 July 2017. The data were collected using a checklist by taking primary data of dysmenorrhea level before and after being given warm compresses of lavender aromatherapy. Analysis data used wilcoxon macth pair test. The result of ststistic test is 0.000 <0.05 so it shows there is difference of dysmenorrhea level before and after given warm compress of aromatherapy lavender in young woman. Thus advised young women can perform dysmenorrhea treatment by giving warm compresses of lavender aromatherapy so that pain can be reduced and can perform activities as usual.